#TITLE_ALTERNATIVE# - PARAMITA (NIM 17304004), WIDYA
Nowadays people in the city have high probability to get stress, it is caused by their lifestyle that forced them to work with high productivity each day. They work hard every day with unfriendly environment such as pollution and traffic jam caused them tired physically and mentally. With the tired body and mind people cannot work optimally so they need an activity to restore their fresh body and mind. Stress cannot be cured only by medicine it also healed by the environment. Traveling and recreation are one of activities to healed stress, people usually take a trip to places that far from the city and has beautiful and relaxing environment. At traveling people need facility such as accommodation which not only gives facility to sleep and eat but also other facility like recreation and relaxation. Resort is one of the accommodation facilities that fill those criteria. In resort there are a lot of recreation and relaxation facilities given to their guests so they will feel comfortable and joyful.